Review and Evaluation of Online Tobacco Dependence Treatment Training Programs for Health Care Practitioners - Selby, Peter; Goncharenko, Karina; Barker, Megan; Fahim, Myra; Timothy, Valerie; Dragonetti, Rosa; Kemper, Katherine; Herie, Marilyn; Hays, J Taylor (JMIR Publications, 2015)
BackgroundTraining health care professionals is associated with increased capacity to deliver evidence-based smoking cessation interventions and increased quit rates among their patients. Online training programs hold promise to provide training but questions remain regarding the quality and usability of available programs. ObjectiveThe aim was to assess the quality of English-language online courses in tobacco dependence treatment using a validated instrument. MethodsAn environmental scan was conducted using the Google search engine to identify available online tobacco dependence treatment courses. The identified courses were then evaluated using the Peer Review Rubric for Online Learning, which was selected based on its ability to evaluate instructional design. It also has clear and concise criteria descriptions to ensure uniformity of evaluations by trained experts. ResultsA total of 39 courses were identified, of which 24 unique courses were assessed based on their accessibility and functionality during the period of evaluation. Overall, the course ratings indicated that 17 of 24 courses evaluated failed to meet minimal quality standards and none of the courses evaluated could be ranked as superior. However, many excelled in providing effective navigation, course rationale, and content. Many were weak in the use of instructional design elements, such as teaching effectiveness, learning strategies, instructor's role, and assessment and evaluation. Evaluation results and suggestions for improvement were shared with course administrators. ConclusionsBased on the courses evaluated in this review, course developers are encouraged to employ best practices in instructional design, such as cohesiveness of material, linearity of design, practice exercises, problem solving, and ongoing evaluation to improve existing courses and in the design of new online learning opportunities.